Mandatory Reporting of Business Responsibility and Sustainability and Stock Market Response: Evidence from an Emerging Economy - Rajesh Desai; Teguh Budiman (Universitas Pasundan, 2024)
The objective of the current study is to evaluate the impact of the mandatory business responsibility and sustainability reporting (BRSR) framework on stock market performance in India. The study uses event study technique to evaluate the impact of this announcement while taking into account a sample of 940 listed Indian companies and daily stock return data from 276 trading days. According to the study's examination of cumulative average abnormal returns (CAAR) and daily average abnormal returns (AAR) for various event windows, stock market participants have positively and strongly reacted to the BRSR announcement. Further, the impact of carbon sensitivity has been evaluated through independent industry-level analyses. Present research assists managers to understand investor perception towards non-financial disclosures which further helps to enhance the firm value and reduce information asymmetry by providing relevant information. Further, policymakers can use findings of present research to disseminate the advantages of adopting ESG disclosure practices. Current study provides pioneering evidence on the market response to compulsory ESG disclosure framework in emerging context. Further, it makes a substantial contribution to the expanding field of sustainability research and has significant policy, managerial, and academic ramifications.